Quick needle insertion at pharyngeal acupoints for poststroke dysphagia: A case report. Issue 50 (December 2017) - Li, Xiaoning; Wu, Lei; Guo, Fan; Liang, Xuesong; Fu, Hao; Li, Nuo
Abstract: Rationale: Dysphagia following stroke is a major complaint among patients, and effective treatment of post-stroke dysphagia can be difficult. We present a case report describing a new treatment for dysphagia, namely, quick needle insertion at pharyngeal acupoints. Patient concerns: A 70-year-old man developed pharyngeal dysphagia after a stroke. Three months after the patient experienced a sudden stroke leading to liquid dysphagia, acupuncture, one of the most important therapies in Traditional Chinese Medicine, was used to treat the patient. Diagnoses: A diagnosis of cerebral infarction and bulbar paralysis was made. Interventions: Quick needle insertion was performed at five pharyngeal acupoints, once a day, 6 times a week for 6 weeks. Outcomes: The patient subsequently showed significant improvement in the pharyngeal phase of swallowing. His performance in the drinking water test reduced to level 1 from level 4. The functional oral intake scale score changed from level 2 to level 7. In the video fluoroscopic swallowing study, no spillage occurred, but aspiration was present. The residue of the contrast agent was reduced. Lessons: Quick needle insertion at pharyngeal acupoints can be an efficient way to treat post-stroke dysphagia.